2022
DOI: 10.1111/brv.12843
|View full text |Cite
|
Sign up to set email alerts
|

Critical thermal limits in ants and their implications under climate change

Abstract: Critical thermal limits (CTLs) constrain the performance of organisms, shaping their abundance, current distributions, and future distributions. Consequently, CTLs may also determine the quality of ecosystem services as well as organismal and ecosystem vulnerability to climate change. As some of the most ubiquitous animals in terrestrial ecosystems, ants are important members of ecological communities. In recent years, an increasing body of research has explored ant physiological thermal limits. However, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 153 publications
2
13
0
Order By: Relevance
“…For example, changes in critical thermal limits have been associated with variations in some aspects of climate, such as precipitation and temperature, which determine species' distribution at both geographic and temporal gradients (e.g. Sunday et al, 2011;Kellermann et al, 2012;García-Robledo et al, 2018;Nascimento et al, 2022). Given that critical thermal limits are good predictors of an organism's potential response to extreme temperature changes, they are commonly used in calculating thermal sensitivity indices, which estimates a population or species' susceptibility to climate change (Deutsch et al, 2008;Sunday et al, 2014;Clusella-Trullas et al, 2021;Roeder et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…For example, changes in critical thermal limits have been associated with variations in some aspects of climate, such as precipitation and temperature, which determine species' distribution at both geographic and temporal gradients (e.g. Sunday et al, 2011;Kellermann et al, 2012;García-Robledo et al, 2018;Nascimento et al, 2022). Given that critical thermal limits are good predictors of an organism's potential response to extreme temperature changes, they are commonly used in calculating thermal sensitivity indices, which estimates a population or species' susceptibility to climate change (Deutsch et al, 2008;Sunday et al, 2014;Clusella-Trullas et al, 2021;Roeder et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Our results support the idea that CT max could be a good predictor of ant activity in semiarid tropical regions. Other studies found that CT max was more strongly associated with microclimatic than macroclimatic gradients (Baudier et al, 2018; Nascimento et al, 2022). This result could explain why CT max is tightly linked to local ant activity.…”
Section: Discussionmentioning
confidence: 88%
“…The CT max is particularly important in the lives of poikilothermic ectotherms (Sinclair et al, 2016; Bennet et al, 2021), whose body temperatures depend exclusively on environmental temperatures. Furthermore, CT max can determine species distribution and abundance at regional and local scales (Deutsch et al, 2008; Kearney & Porter, 2009; Clusella‐Trullas et al, 2011; Buckley et al, 2012; Arnan & Blüthgen, 2015; Sunday et al, 2019), and, ultimately, their responses to disturbance and climate change (Roeder et al, 2021a; Nascimento et al, 2022). Finally, because CT max also affects species performance, activity, and behaviour, it may also impact the outcome of ant‐plant mutualisms (Fitzpatrick et al, 2014; Tamashiro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations